Stamps and Artifacts. Religious Constellations in Chilean Novels of the Last Century - Albornoz Toloza, Valentina (2024)
The space and the objects distributed in it influence the actions of certain characters, creating constellations (Gordillo, 2014), which carry an ideological charge. This paper aims to analyze how some objects belonging to the Catholic religion influence the actions of the characters, both apostates and practitioners within the diegesis, and how they act, allegorizing situations of chaos, violence, and despair (Avelar, 2000). This article is concerned with evidencing this process in the novels Pasión y muerte del cura Deusto (Passion and Death of the Priest Deusto) (1924) by Augusto D’Halmar, Coronación (Coronation) (1957) by José Donoso, Cristianas viejas y limpias (Christian Old and Clean) by Enrique Lafourcade (1997), Cuándo éramos inmortales (When We were Immortal) (1998) by Arturo Fontaine, and Ruido (Noise) (2012) by Álvaro Bisama.